EDACO, a derivative of myricetin, inhibits the differentiation of Gaoyou duck embryonic osteoclasts in vitro. Issue 2 (4th March 2019) - Fu, Y.X.; Wang, Y.H.; Tong, X.S.; Gong, Z.; Sun, X.M.; Yuan, J.C.; Zheng, T.T.; Li, C.; Niu, D.Q.; Dai, H.G.; Liu, X.F.; Mao, Y.J.; et al.
ABSTRACT: 1. This study determined the effects of (E)-3-(2-(4-(3-(2, 4-dimethoxyphenyl)acryloyl)phenoxy)ethoxy)-5, 7-dimethoxy-2-(3, 4, 5-trimethoxyphenyl)-4H-chromen-4-one (EDACO) on the differentiation of Gaoyou duck embryonic osteoclasts cultured in vitro . 2. Bone marrow mononuclear cells (BM-MNC) were collected from 23-d-old Gaoyou duck embryos and induced by macrophage colony-stimulating factor and receptor activator of nuclear factor κB ligand in the presence of EDACO at different concentrations (i.e. 10, 20, 40, 80 and 160 µM). Tartrate-resistant acid phosphatase (TRAP) staining and resorption ability determination were conducted. 3. Results suggested that EDACO suppressed the shaping of positive multinucleated cells and the number of TRAP-positive cells in the 20, 40, 80 and 160 μM EDACO groups was significantly decreased ( P < 0.05 or P < 0.01). Besides, the absorption activity of differentiated duck embryonic osteoclasts was significantly inhibited ( P < 0.05) in both 80 and 160 μM EDACO groups. 4. Overall, EDACO can inhibit the differentiation of BM-MNC into mature osteoclasts in duck embryos.1